The depth of the Rees algebra of three general binary forms. Issue 2 (1st February 2019) - Burity, Ricardo; Simis, Aron
Abstract: One proves that the Rees algebra of an ideal generated by three general binary forms of same degree≥ 5 has depth one. The proof hinges on the behavior of the Ratliff–Rush filtration for low powers of the ideal and on establishing that certain large matrices whose entries are quadratic forms have maximal rank. One also conjectures a shorter result that implies the main theorem of the paper.